2017
DOI: 10.1186/s13071-017-2565-y
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and necroptosis of mouse hippocampal and parenchymal astrocytes, microglia and neurons caused by Angiostrongylus cantonensis infection

Abstract: Background: Angiostrongylus cantonensis has been the only parasite among Angiostrongylidae to cause human central nervous system infection characterized by eosinophilic meningitis or meningoencephalitis. The mechanism of the extensive neurological impairments of hosts caused by A. cantonensis larvae remains unclear. The aim of the present study was to investigate apoptosis, necroptosis and autophagy in the brains of mice infected with A. cantonensis, which will be valuable for better understanding the pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 53 publications
5
24
0
Order By: Relevance
“…Angiostrongyliasis cantonensis infection is a zoonotic disease characterized by neurological manifestations, including eosinophilic meningitis and meningoencephalitis, in nonpermissive hosts (OuYang et al, 2012;Zhang et al, 2017). In the definitive host (the rat), however, there appears to be relatively little eosinophilic inflammation and nerve damage in the CNS from 7 dpi to 21 dpi, as detected by H&E staining (Figure 1), compared to the pathological injuries in nonpermissive hosts, which was in accord with previous studies (Li et al, 2014;Liu et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Angiostrongyliasis cantonensis infection is a zoonotic disease characterized by neurological manifestations, including eosinophilic meningitis and meningoencephalitis, in nonpermissive hosts (OuYang et al, 2012;Zhang et al, 2017). In the definitive host (the rat), however, there appears to be relatively little eosinophilic inflammation and nerve damage in the CNS from 7 dpi to 21 dpi, as detected by H&E staining (Figure 1), compared to the pathological injuries in nonpermissive hosts, which was in accord with previous studies (Li et al, 2014;Liu et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…Rats and mice, which share high nucleotide substitution rates, are rodents that constitute part of the subfamily Murinae of the family Muridae (Blanga-Kanfi et al, 2009;Churakov et al, 2010); they are used in more than 40% of neurological studies (Manger et al, 2008;Krubitzer et al, 2011), are the most widely used animal models for research on vaccine development, drug screening and gene function (Douam and Ploss, 2018), and serve as natural vectors or reservoir hosts for the global transmission and expansion of various infectious pathogens, including bacteria (Du and Wang, 2016), viruses (Forbes et al, 2018;Tanveer et al, 2018), and parasites (Movsesyan et al, 2018). A. cantonensis invasion primarily causes negligible or severe eosinophilic meningoencephalitis and meningitis in the CNS of permissive and non-permissive hosts, respectively (Li et al, 2014;Zhang et al, 2017). Although A. cantonensis is the most common infectious cause of eosinophilic meningitis in Southeast Asia and the Pacific Basin (Dunn et al, 2019) and distinct pathological outcomes of rats and mice with A. cantonensis infection have been observed over the past several decades (Courdurier et al, 1964;Wallace and Rosen, 1969;Uchida et al, 1984), the pathogenicity and pathophysiology of neuro-angiostrongyliasis remain unclear (Morassutti and Graeff-Teixeira, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported the apoptosis and necroptosis of parenchymal and hippocampal astrocytes, neurons, and microglia in mice infected with A. cantonensis [2]. However, we do not know the factors playing a role in apoptosis.…”
Section: Discussionmentioning
confidence: 77%
“…Angiostrongylus cantonensis was previously shown to cause apoptosis and necroptosis in the brains of infected mice; this was associated with elevated cleaved caspase-3, -4, and -6, and receptor-interacting serine/ threonine-protein kinase (RIP)3 mRNA levels, RIP3, and phosphorylated (p)RIP3 protein levels relative to the levels observed in control mice. Furthermore, apoptotic and necrotic microglia, astrocytes, and neurons were observed in the parenchymal and hippocampal regions of infected mice [2].…”
mentioning
confidence: 95%